The Effectiveness of Investigations and Prosecutions of Corruption Crimes by the Corruption Eradication Commission, the Police, and the Prosecutor's Office: A Study of the Power of Power in Criminal Law Enforcement - Rusdi Rusdi; Evita Isretno Israhadi (International Journal of Social Service and Research, 2026)
This research analyzes the effectiveness of investigations and prosecutions of corruption crimes conducted by the Corruption Eradication Commission (KPK), the Indonesian National Police, and the Indonesian Attorney General’s Office, focusing on the dynamics of authority disputes within the national law enforcement system. The multiplicity of law enforcement agencies authorized to investigate corruption has created institutional complexity, disharmony of authority, and potential inter-institutional competition that affect the effectiveness of the case-handling process. This research uses a comparative legal system approach by comparing Indonesia’s multi-agency model with jurisdictions that adopt a single-agency model with exclusive authority in eradicating corruption. The research results show that the effectiveness of investigations and prosecutions conducted by the Corruption Eradication Commission (KPK) is relatively high due to strong regulatory support, independence, and institutional focus on corruption. In contrast, the Police and the Prosecutor’s Office face structural constraints, extensive caseloads, and limited coordination, which affect the quality of case handling. Authority disputes among institutions often give rise to overlapping processes, delays in case handling, and legal uncertainty in determining the most competent institution. Comparisons with other national legal systems show that countries implementing a single-agency model, such as the Corrupt Practices Investigation Bureau (CPIB) in Singapore and the Independent Commission Against Corruption (ICAC) in Hong Kong, are more effective in handling corruption due to clear authority, minimal jurisdictional conflict, and a rapid investigation process. This research concludes that the effectiveness of investigation and prosecution mechanisms in Indonesia needs to be strengthened through the reconstruction of authority design, the strengthening of systemic coordination, and the establishment of clearer jurisdictional boundaries among law enforcement institutions.